IMPLEMENTATION OF CHARACTER EDUCATION MANAGEMENT MODEL IN TECHNOLOGY-ORIENTED LEARNING ERA - Zuhair Mubarrak Hazaa (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
Character education in the world of education in the era of industry 4.0 and technological advances does not seem to be well balanced with the character education process at school. Guardians seem indifferent to their children's learning activities and tend to give children the freedom to explore the world of information without strict supervision from guardians. Character education in pesantren is one option to educate and instill the character of students. This can be implemented because the character education process in pesantren is managed by the pesantren dormitory education system. Researchers used observation and interview methods with pesantren managers, student guardians and students. After collecting data, researchers found that character education can only be carried out if students are in a pesantren education environment. The pattern of pesantren education is to build the character of students to become moral, ethical, polite, trustworthy, honest humans, have general and special skills, be able to communicate well, maintain religious norms in life. Character education will be realized if students have knowledge and are educated in the pesantren education system that conducts 24-hour supervision every day.